E-Cadherin Suppresses Cellular Transformation by Inhibiting β-Catenin Signaling in an Adhesion-Independent Manner - Gottardi, Cara J. (The Rockefeller University Press, 2001)
E-cadherin is a tumor suppressor protein with a well-established role in cell–cell adhesion. Adhesion could contribute to tumor suppression either by physically joining cells or by facilitating other juxtacrine signaling events. Alternatively, E-cadherin tumor suppressor activity could result from binding and antagonizing the nuclear signaling function of β-catenin, a known proto-oncogene. To distinguish between an adhesion- versus a β-catenin signaling–dependent mechanism, chimeric cadherin constructs were expressed in the SW480 colorectal tumor cell line. Expression of wild-type E-cadherin significantly inhibits the growth of this cell line. Growth inhibitory activity is retained by all constructs that have the β-catenin binding region of the cytoplasmic domain but not by E-cadherin constructs that exhibit adhesive activity, but lack the β-catenin binding region. This growth suppression correlates with a reduction in β-catenin/T cell factor (TCF) reporter gene activity. Importantly, direct inhibition of β-catenin/TCF signaling inhibits the growth of SW480 cells, and the growth inhibitory activity of E-cadherin is rescued by constitutively activated forms of TCF. Thus, the growth suppressor activity of E-cadherin is adhesion independent and results from an inhibition of the β-catenin/TCF signaling pathway, suggesting that loss of E-cadherin expression can contribute to upregulation of this pathway in human cancers. E-cadherin–mediated growth suppression was not accompanied by overall depletion of β-catenin from the cytosol and nucleus. This appears to be due to the existence of a large pool of cytosolic β-catenin in SW480 cells that is refractory to both cadherin binding and TCF binding. Thus, a small pool of β-catenin that can bind TCF (i.e., the transcriptionally active pool) can be selectively depleted by E-cadherin expression. The existence of functionally distinct pools of cytosolic β-catenin suggests that there are mechanisms to regulate β-catenin signaling in addition to controlling its level of accumulation.